STANDARDIZATION OF HOUSEHOLD INDUSTRIAL PRODUCTS IN PERJUANGAN TELUK NIBUNG TANJUNG BALAI - Ivanna, Julia; Irfandi, Irfandi; Rangkuti, Aswin (Universitas Negeri Medan, 2019)
This community service activity was carried out in Perjuangan, Teluk Nibung District, Tanjung Balai City, which is 5 km to the capital city of the sub-district. The partners are home industries namely Edelwis Family Income Improvement Partners (UPPKS) managed by Ms. Pait Mawan who is engaged in Fish Culinary and Shellfish Handicrafts. The problems faced by partners are lack of partner knowledge about attractive product packaging design, halal certification process of products, alternative marketing, and financial statement preparation. The products produced are not able to compete with similar products marketed in the modern market so that they are only marketed in stalls around the village and traditional markets because they do not have packaging designs and halal certificates. This certainly hampers the increase in income of both partners. In connection with the problems faced by partners, the community service standards and halal certification of LPPOM MUI products, attractive packaging designs, bookkeeping training, and online marketing will be realized. The methods used to achieve the objectives of this service activity are education, socialization, product standardization assistance, bookkeeping and business management training, online marketing training. The level of success of the community service activities of this BOPTN fund will be measured from the results: 1) Packaging Design, 2) Halal Certificates from LPPOM MUI, 3) Financial Reports, 4) Online Shop Accounts.Keywords: Assistance, Packaging Design, Halal Certification, Financial Reports, Online Marketing.